Anomaly of Pyrano[2, 3‐c]pyrazole Synthesis towards Pyrazolyl‐aryl‐methyl‐malononitrile Derivatives and Their Antimicrobial Activity. Issue 23 (14th June 2022) - Mokariya, Jaydeep A.; Rajani, Dhanji P.; Patel, Manish P.
Abstract: Our attempt to prepare pyrano[2, 3‐c]pyrazole derivatives from 2‐methyl‐5‐propyl‐1, 2‐dihydro‐pyrazolone, malononitrile and benzaldehyde rather lead to the formation of pyrazolyl‐aryl‐methyl‐malononitrile derivatives. Fascinating by this opportunity to branch out the synthesis of substituted pyrazolone derivatives using an efficient multicomponent synthetic approach for pyrazolyl‐aryl‐methyl‐malononitrile derivatives. The synthesis was accelerated using guanidine carbonate as a catalyst in the water reaction medium. The rection has blossomed with the green aspects of synthesis such as organocatalyst, water as reaction medium and ambient temperature providing clean product in higher yield. The synthesized derivatives have been screened for anti‐microbial activity. Compounds 4  c and 4  n showed excellent activity. Six compounds were found to be much effective against the Staphylococcus aureus bacterial strain. The molecular docking study of 4  n showed a high binding affinity with the receptor. Collectively, our study provides eco‐friendly synthesis towards pyrazolyl‐aryl‐methyl‐malononitrile derivatives and we evaluated them as a new class of anti‐microbial compounds. Abstract : The key pharmacophore 2‐methyl‐5‐propyl‐1, 2‐dihydro‐3H‐pyrazol‐3‐one reacts with malononitrile and benzaldehyde in a water‐mediated guanidine carbonate catalysed multicomponent reaction, yielding pyrazolyl‐aryl‐methyl‐malononitrile derivatives in excellent yield. These compounds are intermediates in the synthesis of pyrazno[2, 3‐c]pyrazole. The compounds were tested for antibacterial activities against three gram‐positive and three gram‐negative bacterial strains, and they were found to be most effective against Staphylococcus aureus strain.